2017
DOI: 10.1038/ncomms14260
|View full text |Cite
|
Sign up to set email alerts
|

A metastable liquid melted from a crystalline solid under decompression

Abstract: A metastable liquid may exist under supercooling, sustaining the liquid below the melting point such as supercooled water and silicon. It may also exist as a transient state in solid–solid transitions, as demonstrated in recent studies of colloidal particles and glass-forming metallic systems. One important question is whether a crystalline solid may directly melt into a sustainable metastable liquid. By thermal heating, a crystalline solid will always melt into a liquid above the melting point. Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
6
20
1
Order By: Relevance
“…In Figure 2, the progress of two-step decelerated melting observed through 29 Si NMR (c) and IXS experiments (d) is shown for Na zeolite Y. From NMR spectra, the 5 Si-Al configurations are readily identified in the starting crystal and are still evident ( Figure S6, Supporting Information) even when only 25% of Na zeolite Y remains, confirming that crystalline topology is retained in the initial LDA phase (c).…”
Section: Signature Of Meltingmentioning
confidence: 81%
See 2 more Smart Citations
“…In Figure 2, the progress of two-step decelerated melting observed through 29 Si NMR (c) and IXS experiments (d) is shown for Na zeolite Y. From NMR spectra, the 5 Si-Al configurations are readily identified in the starting crystal and are still evident ( Figure S6, Supporting Information) even when only 25% of Na zeolite Y remains, confirming that crystalline topology is retained in the initial LDA phase (c).…”
Section: Signature Of Meltingmentioning
confidence: 81%
“…Static photoluminescence excitation (PLE) and emission spectra (PL) were recorded on compressed powders of 5 mm in diameter (produced by uniaxial compaction at 1 GPa), using a high-resolution spectrofluorometer (Fluorolog 3, Horiba) with a continuous-wave 450 W Xe lamp as excitation source, and a Hamamatsu R2658P photomultiplier tube (PMT) for detection. 29 Si magic angle spinning NMR measurements ( Figure S6, Supporting Information) were recorded on a Bruker Advance DSX 400 9.4 T spectrometer. Using the excitation line of 7 F 0 → 5 L 6 at the wavelength of 393 nm, the intensity ratio of the emission bands of 5 D 0 → 7 F 2 (≈612 nm) and 5 D 0 → 7 F 1 (≈591 nm) was determined as a measure of local ligand symmetry.…”
Section: Xrd Collapse Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results have demonstrated that an intermediate liquid phase seems to appear often during the solid–solid phase transition, acting as a precursor to induce the nucleation of the second solid phase in colloidal systems and a bulk metallic glass . The same phenomenon was also observed in a high‐pressure crystalline phase of bismuth (Bi), which can melt into a metastable liquid phase below the melting line during the decompression process . The metastable liquid can be kept for several hours at static conditions and transform into crystalline phases under external perturbations such as heating or cooling.…”
Section: Liquid–liquid Transition In Metallic Liquidsmentioning
confidence: 89%
“…It is also of significant importance in alloy design and in the control of single crystal growth. Various crystallization pathways and growth mechanisms of deeply supercooled [1][2][3][4], supersaturated [5,6], and even super-compressed [7][8][9] metastable phases were extensively reported based on various experimental techniques using electrostatic levitation (ESL), electromagnetic levitation (EML), aerodynamic levitation (ADL), and diamond anvil cell (DAC).…”
Section: Introductionmentioning
confidence: 99%